Chitosan based ZnO nanoparticles loaded gallic-acid films for active food packaging. (1st January 2021) - Yadav, Srasti; Mehrotra, G.K.; Dutta, P.K.
Highlights: Physicochemical and mechanical properties of chitosan films containing ZnO@gal were investigated. ZnO@gal improved antioxidant property as well as antibacterial property. ZnO@gal improved mechanical properties of the film as well as WVP. The fabricated bio-composite films indicated considerable potential for food packaging. Abstract: Chitosan (Ch) and zinc oxide nanoparticles loaded gallic-acid films, (Ch-ZnO@gal) have been prepared aiming for their exploitation as environmentally benign food packaging material. The chitosan films with varying quantities of zinc oxide nanoparticles loaded gallic-acid (ZnO@gal) content were synthesized in order to evaluate the effect of ZnO@gal on their optimum mechanical and biological potential. The characteristic results have shown that the incorporation of ZnO@gal into chitosan films remarkably enhanced the desired mechanical property of the chitosan films. Other noticeable physical properties such as oxygen and water vapor permeability (WVP), swelling, water solubility and UV–vis light transmittance have also been found to improve positively. SEM analysis of the films indicates a good material compatibility between chitosan and ZnO@gal matrices. Ch-ZnO@gal films possess significant antibacterial potential and strong antioxidant behavior compared to pristine chitosan. The overall results suggested that the prepared biocomposite chitosan films may be considered for active food packaging applications.